2013
DOI: 10.1111/ctr.12151
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus leads to a lower risk of BKV viremia than mycophenolic acid in de novo renal transplantation patients: a single‐center experience

Abstract: These findings suggest that in comparison with MPA and Cya, an EVR and LD-CyA regimen lowers the risk of BKV viremia after kidney transplantation and favorably alters outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 32 publications
(35 reference statements)
0
45
1
Order By: Relevance
“…BKV clearance was reported in five and significant reduction in viremia in the remaining four RTR . Everolimus with low dose Cs A was found to be associated with lower incidence of BKVN compared with Cs A and MPA combination in new RTR . A larger study of everolimus is under way at the University of California, San Francisco (http://ClinicalTrials.gov, identifier: NCT01624948).…”
Section: Treatment Of Bk Virus Nephropathymentioning
confidence: 99%
See 1 more Smart Citation
“…BKV clearance was reported in five and significant reduction in viremia in the remaining four RTR . Everolimus with low dose Cs A was found to be associated with lower incidence of BKVN compared with Cs A and MPA combination in new RTR . A larger study of everolimus is under way at the University of California, San Francisco (http://ClinicalTrials.gov, identifier: NCT01624948).…”
Section: Treatment Of Bk Virus Nephropathymentioning
confidence: 99%
“…41 Everolimus with low dose Cs A was found to be associated with lower incidence of BKVN compared with Cs A and MPA combination in new RTR. 42 A larger study of everolimus is under way at the University of California, San Francisco (ClinicalTrials.gov, identifier: NCT01624948). Another open-label, randomized, prospective study of substitution of Tac by sirolimus, in preventing BKVN in patients with BK viremia, is being carried out by Columbia University.…”
Section: Treatment Of Bk Virus Nephropathymentioning
confidence: 99%
“…A number of studies have shown that the use of mammalian target of rapamycin inhibitors mTOR results in reduced rates of CMV infection . Similarly, there is evidence to suggest that mTOR inhibitors may inhibit BK viral replication, whereas tacrolimus exerts the opposite effect …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Similarly, there is evidence to suggest that mTOR inhibitors may inhibit BK viral replication, whereas tacrolimus exerts the opposite effect. 8,9 In this retrospective single-center review, we investigate if conversion into an mTOR inhibitor and reduced-dose tacrolimus (TAC-mTOR) at 1 month post-transplantation could lower the risk of viral infections after KP transplantation compared to standard tacrolimus and mycophenolate mofetil (TAC-MMF) immunosuppression. Board approved this study.…”
Section: Introductionmentioning
confidence: 99%
“…Because BKV is of particular significance in ABO‐i patients, who are at higher risk given their high immunosuppression burden , we focused on the effect of conversion to EVR regarding the BK virus. It has been shown that conversion to mTOR inhibitor‐based maintenance immunosuppression after kidney transplantation is correlated with a lower incidence of BKV viremia and that EVR leads to a lower risk of BKV viremia compared with MPA . Patients on a Tac‐MPA regimen are at higher risk of developing BKV viremia than patients receiving Tac‐EVR.…”
Section: Discussionmentioning
confidence: 99%